Islamic Banking Fiqh: Urgency and Economic Challenges in the System of Islamic Financial Institutions (LKS) in Indonesia - Tentiyo Suharto (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Islamic banking is a form of financial system based on sharia principles. The urgency of fiqh in Islamic banking is very important because it is a guideline in carrying out transactions in accordance with Islamic law. One of the important aspects in Islamic banking is the application of fiqh muamalah in the products of raising funds (funding), channeling funds (landing) and services (services) in the payment traffic offered. This research uses a qualitative method. Data were collected through literature review, analysis of bank policy documents related to products at Islamic financial institutions (LKS). The result of this study is that although the application of Islamic banking fiqh has been running well, especially in relation to murabahah, mudharabah, musyarakah, ijarah, kafalah, wakalah and hiwalah contracts, it has been applied in accordance with the principles of Islamic banking fiqh. However, there are still some challenges such as the public's not optimal understanding of the concept of Islamic banking, especially in LKS, regulations that continue to evolve, and competition with conventional banking or conventional financial institutions that still require increased education to the public as well as strengthening regulations to ensure compliance with sharia principles. To be able to contribute to the development of Islamic banking specifically in the field of LKS in Indonesia.